2014
DOI: 10.4168/aair.2014.6.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Specific Immunotherapy for Allergic Rhinitis: A Survey of Chinese ENT Specialists

Abstract: PurposeSpecific immunotherapy (SIT) is a suitable but uncommon treatment option for allergic rhinitis (AR) in China. The current understanding and attitude of Chinese ENT (ear, nose, and throat) specialists in regards to SIT is unclear. This study investigates current trends in the awareness and application status of SIT among Chinese ENT specialists.MethodsWe performed a nationwide, cross-sectional survey with a specially designed questionnaire given to 800 ENT specialists in China. A member of the trained re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Subcutaneous injection of allergen extract, also known as allergy shots, has since been the historical and predominant method of administration. Indeed, a nationwide cross-sectional survey assessing the trends in specific immunotherapy for AR in China has recently shown that conventional subcutaneous injection was the treatment option, which was most highly recommended by 96.2% of the Chinese ENT Specialists surveyed (30). However, sublingual immunotherapy (SLIT) has rapidly been established with high scientific credibility and become the most viable alternative to SCIT.…”
Section: Modifying Effect Of Ait On Allergic Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Subcutaneous injection of allergen extract, also known as allergy shots, has since been the historical and predominant method of administration. Indeed, a nationwide cross-sectional survey assessing the trends in specific immunotherapy for AR in China has recently shown that conventional subcutaneous injection was the treatment option, which was most highly recommended by 96.2% of the Chinese ENT Specialists surveyed (30). However, sublingual immunotherapy (SLIT) has rapidly been established with high scientific credibility and become the most viable alternative to SCIT.…”
Section: Modifying Effect Of Ait On Allergic Diseasementioning
confidence: 99%
“…However, sublingual immunotherapy (SLIT) has rapidly been established with high scientific credibility and become the most viable alternative to SCIT. As house dust mites (HDM) have been shown to be the most prevalent allergens in patients with AR and atopic asthma in multi-center study of prevalence of sensitization in patients with AR and atopic asthma in Mainland China (20), the Chinese guidelines recommend that AR patients who are allergic to one or two aeroallergens and particularly sensitized to HDM, should be treated by AIT (30).…”
Section: Modifying Effect Of Ait On Allergic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ENT specialists are mainly responsible for the primary treatment of AR. In this regard, important information has been provided by a Chinese survey conducted among ENT specialists on their knowledge and clinical usage of SIT 12. Most of the survey respondents considered AR (96.0%) and allergic asthma (96.0%) the most suitable indications for SIT.…”
mentioning
confidence: 99%
“…In contrast, the predominant view in the United States is that one should treat as many of a patient's allergies as possible by administering all the relevant allergens (either as a mixture or as separate extracts). Data suggest that ENT specialists in China tend to use a similar SIT approach to treating patients as that used in the United States 12. According to published data, the use of single- or multi-antigen immunotherapy in polysensitized patients, whether delivered sublingually or subcutaneously, requires more supporting data 20…”
mentioning
confidence: 99%